Service production and intellectual property. (1st January 2000) - Miles, Ian; Andersen, Birgitte; Boden, Mark; Howells, Jeremy
Service firms and sectors are emerging as important players in the innovation process. The intangible nature of many service innovations creates challenges for Intellectual Property Right (IPR) systems. IPR systems both shape and are shaped by structural changes in the economy, and the technologies being employed. It is well known that many service firms do not patent, and that the patent system has largely been developed to deal with more tangible innovations. This study considers the issues that arise in this context. It presents empirical material concerning the management of knowledge, innovation, and Intellectual Property in Knowledge Intensive Business Services (KIBS). Different branches of the service sector are founded on very different knowledge bases; and there are also persistent differences in the activities performed by service firms of different sizes. Accordingly, though they have much in common where it comes to the management of expertise and the use of Information Technology (IT), they may follow dissimilar innovation trajectories, and adopt highly variegated strategies.